Nitrogen and copper-doped carbon quantum dots with intrinsic peroxidase-like activity for double-signal detection of phenol. Issue 13 (9th June 2021) - Du, Jinyan; Qi, Shuangqing; Fan, Tingting; Yang, Ying; Wang, Chaofeng; Shu, Qin; Zhuo, Shujuan; Zhu, Changqing
Abstract : Using the oxidative coupling reaction of phenol with 4-AAP in the presence of H2 O2 catalyzed by N, Cu-CQDs with an intrinsic peroxidase-like activity, a new sensing system with double signals was constructed for the detection of phenol. Abstract : Herein, a simple and facile one-step hydrothermal carbonization synthesis procedure for the fabrication of N, Cu-doped carbon quantum dots (N, Cu-CQDs) as a peroxidase-mimicking enzyme was reported. The peroxidase-like performance of N, Cu-CQDs was assessed based on the oxidative coupling reaction of phenol with 4-aminoantipyrine (4-AAP) in the presence of hydrogen peroxide (H2 O2 ). The N, Cu-CQDs/4-AAP/H2 O2 system was applied to sensing phenol based on double signals of absorption spectra (or colorimetric visualization) as well as fluorescence spectra. The obtained limits of detection (LODs) were as low as 0.12 μM and 0.02 μM, respectively. Moreover, the proposed method was successfully applied to the determination of phenol in sewage with satisfactory recovery. Our results demonstrate that the N, Cu-CQDs/4-AAP/H2 O2 /phenol sensing system has a great potential prospect for applications in environmental chemistry and biotechnology.